1992
DOI: 10.2214/ajr.159.3.1503016
|View full text |Cite
|
Sign up to set email alerts
|

Acute lower gastrointestinal hemorrhage: treatment by superselective embolization with polyvinyl alcohol particles.

Abstract: OBJECTIVE. The major risk of transcatheter embolotherapy for acute hemorrhage in the lower gastrointestinal tract is irreversible intestinal ischemia. The authors studied the efficacy and safety of superselective transcatheter embolization with polyvinyl alcohol particles in arresting acute hemorrhage in the lower gastrointestinal tract. SUBJECTS AND METHODS. All patients with clinical or scintigraphic evidence of acute hemorrhage in the lower gastrointestinal tract were considered for superselective embolizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
68
1
2

Year Published

1994
1994
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(71 citation statements)
references
References 0 publications
0
68
1
2
Order By: Relevance
“…Acute surgical intervention will eventually be required in 10%-15% of patients, 7 but is associated with a mortality of 25%. 8 Mesenteric angiography and angioembolization is a well described diagnostic and therapeutic option in the management of both acute UGIB [9][10][11][12] and LGIB [13][14][15][16] after endoscopic failure. The decision to perform mesenteric angiography or proceed directly with surgical intervention is often at the discretion of the attending surgeon.…”
mentioning
confidence: 99%
“…Acute surgical intervention will eventually be required in 10%-15% of patients, 7 but is associated with a mortality of 25%. 8 Mesenteric angiography and angioembolization is a well described diagnostic and therapeutic option in the management of both acute UGIB [9][10][11][12] and LGIB [13][14][15][16] after endoscopic failure. The decision to perform mesenteric angiography or proceed directly with surgical intervention is often at the discretion of the attending surgeon.…”
mentioning
confidence: 99%
“…33 The long-term consequences of angiographic control of hemorrhage are unknown, but the colon appears to be at increased risk for ischemia and colonic stricture after transcatheter embolization. 34,35 In our study, we found that 6 of the 20 patients who received vasopressin still required urgent operation after the infusion was initiated, and 8 of the remaining 14 patients ultimately underwent a colon resection. Seventy percent of our patients in this group, therefore, had surgery.…”
Section: Commentmentioning
confidence: 65%
“…The use of superselective embolisation to deliver particulate size of 100 µm or larger 4 into the most distal arterial branches has resulted in a reduction of this complication with only 10% requiring surgery for ischaemia. 5 Moreover, the combination of particulate and microcoil superselective embolisation may be advantageous in controlling haemorrhage caused by diffuse lesions such as vascular malformations with minimal amount of embolysates, reducing further the risk of infarction. 6 Surgery is indicated for persistent haemorrhage, re-bleeding and signs of colonic ischaemia post embolisation.…”
Section: Discussionmentioning
confidence: 99%